UNIX Internals and network programming, December 12-16, 1992 : part of the UNIX course - CICC (Japan); Fujitsu Systems Business (Malaysia) Sdn. Bhd.; Universiti Teknologi Malaysia. Fakulti Sains Komputer dan Sistem Maklumat (Skudai : UTM, 1992)
57